ANALISIS PROFITABILITAS SEBELUM DAN SESUDAH MERGER ATAU AKUISISI PADA PERUSAHAAN MANUFAKTUR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Aris Setia Noor; Berta Lestari (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2020)
This research aims to know difference or indifference of profitability for 3 years before and after doing merger or acqutitions at food and beverage manufacturing companies listed in Indonesian Stock Exchange. The population in this research is food and beverage companies once doing merger or acquitition, consist of 3 companies. The object of this research is the annual financial statement which are reported in IDX. The test of differences between profitability before and after doing merger or acqutition by using parametric statistical named paired sample t-test for the profitability before and after merger or acqutition in a normal distribution. From result analysis data, NPM, ROI, ROE except OPM accepted hypotesis zero and it means no difference of the profitability for 3 years before and after doing merger or acqutition. This matter can be seen from t count is smaller than the t table. From the analysis, it can be concluded that the profitability of company after merger or acqutition is less than before merger or acqutition. So that the economy target from merger or acqutition is to find added value or synergy is not success. This matter is probably caused by non-economic reasons which is done in order to save the company target from bacnkrupty threat.